(untitled) (Journal of Engineering, 2023)
The advancement of cement alternatives in the construction materials industry is fundamental to sustainable development. Geopolymer is the optimal substitute for ordinary Portland cement, which produces 80% less CO2 emissions than ordinary Portland cement. Metakaolin was used as one of the raw materials in the geopolymerization process. This research examines the influence of three different percentages of sulfate (0.00038, 1.532, and 16.24) % in sand per molarity of NaOH on the compressive strength of metakaolin-based geopolymer mortar (MK-GPM). Samples were prepared with two different molarities (8M and 12M) and cured at room temperature. The best compressive strength value (56.98MPa) was recorded with 12M with lower sulfate content (0.00038%) at 28 days. Also, an inverse relationship is recorded between the increasing sulfate percentages in the sand and the compressive strength values of (MK-GPM). A higher reduction in the compressive strength results at 28 days (60.88% per 8M/NaOH) and (62.23% per 12M/NaOH) was associated with a higher percentage of SO3 in the sand (16.24%).